EPISTEMOLOGI PENDIDIKAN ISLAM: ANALISIS KONSEPTUAL TERHADAP INTEGRASI WAHYU DAN AKAL DALAM PEMBENTUKAN KARAKTER MUSLIM - Indah, Astrid Veranita (Islamijah: Journal of Islamic Social Sciences, 2025)
This study aims to analyze the epistemological construction of Islamic education through the examination of the integration of revelation and reason in the formation of a holistic and contextual Muslim character. The research methodology uses a qualitative approach with library research that analyzes classical and contemporary literature on Islamic epistemology. Content analysis techniques with a hermeneutic approach are applied to interpret fundamental meanings in Islamic epistemological texts. The findings of the study reveal that the epistemology of Islamic education has distinctive characteristics that integrate revelation as a primary source of knowledge with reason as an instrument of interpretation within the framework of the monotheistic paradigm. This integration is realized through the harmonization of bayani (explanatory), burhani (demonstrative), and irfani (intuitive) methodologies that produce a comprehensive knowledge system. The implementation of Islamic epistemology in the formation of Muslim character shows significant relevance in facing the challenges of globalization and the digital era through the development of graduates who have intellectual competence, moral integrity, and balanced spirituality. This study concludes that the epistemology of Islamic education offers an alternative educational paradigm that is able to accommodate the advancement of science without sacrificing Islamic spiritual and ethical values.